Analisis Wacana Kritis Dalam Pidato Joko Widodo Tentang Undang-Undang Cipta Kerja, - Kalvintinus Ndruru; Bimerdin Daely; Helnanirma S. Fau; Agustinus Duha; Merdina Ziraluo; Anita Zagoto (Journal on Education, 2024)
This research aims to describe the structure in the text of President Joko Widodo's speech regarding the Job Creation Law according to van Dijk's study, and to determine the characteristics of AWK in President Joko Widodo's speech regarding the Job Creation Law. This research uses a qualitative descriptive research design with the van Dijk AWK model. Data in the form of the text of President Joko Widodo's speech regarding the Job Creation Law was collected using the documentation method. All data in this study was analyzed using qualitative descriptive techniques. The results of the research show that (1) Based on the structural analysis in the text of President Joko Widodo's speech regarding the Job Creation Law according to van Dijk's study, it shows that the two speech texts are in line with van Dijk's three discourse structures (macro, supra and micro structures).